Blood lead concentrations and attention deficit hyperactivity disorder in Korean children: a hospital-based case control study - Park, Jae Hong (BMC Pediatr, 2016)
BACKGROUND: Because the developing brain of a child is vulnerable to environmental toxins, even very low concentration of neurotoxin can affect children’s neurodevelopment. Lead is a neurotoxic heavy metal which has the harmful effect on the striatal-frontal circuit of brain. This area of the brain is known to be closely related to attention deficit hyperactivity disorder (ADHD) pathophysiology. The primary objective of the present study was to investigate whether elevated blood lead concentration is a risk factor for ADHD. The secondary objective was to examine the association between blood lead concentration and symptom severity. METHODS: We conducted a frequency-matched, hospital-based case-control study with 114 medically diagnosed ADHD cases and 114 controls. The participants were matched for age and sex. The diagnoses of ADHD were assessed with semi-structured diagnostic interviews. The participants completed the continuous performance test (CPT), and their parents completed the ADHD-rating scale (ADHD-RS). Blood lead concentrations were measured by using graphite furnace atomic absorption spectrometry featuring Zeeman background correction. RESULTS: Children with ADHD exhibited blood lead concentrations that were significantly higher than those of the controls ( 1.90 ± 086 μg/dℓ vs. 1.59 ± 0.68 μg/dℓ, p = 0.003). The log transformed total blood lead concentration was associated with a higher risk of ADHD (OR: 1.60, 95 % CI: 1.04–2.45, p < 0.05). The analysis also revealed that the children with blood lead concentrations above 2.30 μg/dℓ were at a 2.5–fold (95 % CI: 1.09–5.87, p < 0.05) greater risk of having ADHD. After adjusting for covariates, our multivariate regression models indicated that blood lead concentrations were not significantly associated with ADHD-RS or CPT profiles among the ADHD cases. CONCLUSION: Even low blood lead concentrations are a risk factor for ADHD in children. This study warrants primary prevention policies to reduce the environmental lead burden. Future studies may be required to ascertain the effects of lead on symptom severity in ADHD.